Sovereignty at sea: The law and politics of saving lives in the Mare Liberum - Thomas Gammeltoft-Hansen; Tanja Aalberts (Danish Institute for International Studies (DIIS), 2010)
Every year between 100,000 and 120,000 migrants attempt to irregularly cross the Mediterranean to reach European shores in hope of political asylum or just a better life. In this working paper Thomas Gammeltoft-Hansen and Tanja Aalberts take on the complicated politics and law of 'rescue at sea', and the legal duty to render assistance to migrants in distress at sea that falls upon all sovereign states. Yet, exactly because this takes in international waters, the precise division and content of this sovereign responsibility remains contested and subject to varying interpretations. As a result, the drowning migrant finds herself subject to an increasingly complex field of governance, in which participating states may successfully barter off and deconstruct responsibility by reference to traditional norms of sovereignty and international law. This working paper is the first in a special series linked to the DIIS research initiative 'Shifting Sovereignties & Power'. The present paper was presented at the first international workshop in this framework titled 'Sovereignty, Territory and Emerging Geopolitics' held at DIIS, 3-4 May 2010
Keywords: 330; Flüchtlinge; Seerecht; Mittelmeer; Einwanderungsrecht; EU-Staaten